Complete the point-slope equation of the line through (1,0)(1,0)(1,0)left parenthesis, 1, comma, 0, right parenthesis and (6,−3)(6,-3)(6,−3)left parenthesis, 6, comma, minus, 3, right parenthesis. Use exact numbers. y−(−3)=y-(-3)=y−(−3)=y, minus, left parenthesis, minus, 3, right parenthesis, equals

Respuesta :

Answer:

[tex]y-(-3)=-\frac{3}{5}(x-6)[/tex]

Step-by-step explanation:

We are given that the line is passing through the point (1,0) and (6,-3).

We have to find the point- slope equation of the line.

Slope formula:

[tex]m=\frac{y_2-y_1}{x_2-x_1}[/tex]

By using the formula

Slope of the line,[tex]m=\frac{-3-0}{6-1}=-\frac{3}{5}[/tex]

Point- slope equation of line with slope m and passing through the point [tex](x_1,y_1)[/tex] is given by

[tex]y-y_1=m(x-x_1)[/tex]

Using the equation,

The equation of the line passing through the point (6,-3) with slope[tex]-\frac{3}{5}[/tex]

[tex]y-(-3)=-\frac{3}{5}(x-6)[/tex]

This is required equation of the  given line.

Answer:

y-(-3)=-0.6(x-6)

Step-by-step explanation: